Abandoned Urban Heritage: Silent Still or Vocal Anew: An Investigation on Taiyanggou Block and Lüshun Industrial School Site (Dalian, China) (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2021)
It is a common understanding to protect the urban heritage allover the world. In fact, some of them are preserved well but others are undergoing the decline and become deserted, even if on the legal protection list. What is the fate of these ‘abandoned’ urban heritage in the future: silent still or vocal anew? Taking Lüshun Industrial School Site (China) as a case study, this paper aims to arouse more attention to the conservation of inconspicuous historical buildings and blocks. Firstly, it introduces the formation and transformation of Taiyanggou area in Lüshun. Then it analyses the survey findings, causes of the ‘abandoned’, and opportunities of the revitalization. Finally, it indicates the significance of analysis on urban context as well as the localized policy in the conservation of urban relics.